2024
DOI: 10.1007/s10257-023-00652-0
|View full text |Cite
|
Sign up to set email alerts
|

Teleworking antecedents: an exploration into availability bias as an impediment

Marie-E. Godefroid,
Vincent Borghoff,
Ralf Plattfaut
et al.

Abstract: Telework technologies have been known since the 1970s, yet their adoption levels remained low until Covid-19-related lockdowns and curfews. The known rational and non-rational technology acceptance theory and biases cannot fully explain this effect. One of the possible answers to fill this gap could be availability bias which has probably also affected the lag in adopting other technologies. To examine this phenomenon, we conducted a qualitative study with 22 interviews with individuals from different organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 113 publications
0
0
0
Order By: Relevance
“…It has also been suggested that the effect of telework is such that, after the COVID-19 crisis, "the future of work is being redesigned by the world's largest telework experiment as a consequence of the global pandemic" (Caraiani et al 2023). Accordingly, although telework-enabling technologies have been known since as early as the 1970s, their level of wide adoption in workplaces remained low until the advent of the COVID-19 crisis (Godefroid et al 2024).…”
Section: Related Evidence From Recent Literature On Telework In the C...mentioning
confidence: 99%
“…It has also been suggested that the effect of telework is such that, after the COVID-19 crisis, "the future of work is being redesigned by the world's largest telework experiment as a consequence of the global pandemic" (Caraiani et al 2023). Accordingly, although telework-enabling technologies have been known since as early as the 1970s, their level of wide adoption in workplaces remained low until the advent of the COVID-19 crisis (Godefroid et al 2024).…”
Section: Related Evidence From Recent Literature On Telework In the C...mentioning
confidence: 99%